Current approaches to managing of advertising and marketing activity - Viatkin, Pavlo; Viatkina, Tetiana; Zdorenko, Tetiana (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2015)
This paper is a research of managing of advertising and marketing company’s activity. It describes main trends in modern advertising mechanisms. Processes of advertising and marketing company’s activity was developed. It was noted that determination of economic and communicative efficiency of implementation of promotional activities is a complex and time-consuming process. It allows evaluating the timeliness and quality of the advertising campaign, no matter what goal it is pursued: the market launch of a new product, attract customers to additional consumption of already known product, acquisition of company image, etc. In addition, evaluation of the effectiveness of promotional activities will help achieve advertising goals faster and at lower cost. As a result, the advertising management mechanism was proposed